The formation of friendships and social mixing in a multiracial neighbourhood in the south of Johannesburg. - Jewan, Rupti (My University, 2009)
The transition of neighbourhoods in post apartheid South Africa has not received adequate attention. Mondeor, a previously White populated suburb in the South of Johannesburg has been identified as progressively diverse in respect of racially diverse neighbourhoods in the aftermath of Apartheid. By focusing on this suburb, the current study investigated whether increased contact with members from different race groups in a residential neighbourhood promotes the formation of inter-racial friendships and social mixing. In addition, it explored whether there were particular associations which promoted interracial friendships or social mixing. Finally, the different types of contact occurring within the suburb were explored. In order to address the above questions the study followed a Qualitative Cross Sectional design. Data for the study was attained through in-depth interviews from twenty residents of Mondeor. The sample was further divided into five participants from each of the four major race groups prevalent in South Africa( African Black, White, and Indian and so-called Coloured). The results from this study found that racial proximity facilitated for much social mixing and a few friendship formations. Closer examination found that there was a reluctance to mix in the suburb however religious and educational institutions as well as recreational facilities in the neighbourhood promoted some integration in the area. In conclusion, the area was racially diverse however not significantly integrated.
Keywords: Contact; Desegregation; Segregation; Friendship